A Study of The Correlation Between Achievement Motivation, Self-Concept, Socioeconomic Status And English Learning Achievement of The Second Year Students of Smp Negeri 3 Bulukumba - Hajriah, Ria (International Journal of English Education and Linguistics (IJoEEL), 2020)
This study was conducted to find out the students’ achievement motivation in learning English, to find out the students’ self-concept in learning English, to find out the students’ socioeconomic status, to find out the students’ English learning achievement. To analyze the correlation between students’ achievement motivation and English learning achievement, to analyze the correlation between students’ self-concept and English learning achievement and to analyze the students’ socioeconomic status and English learning achievement.This study employed correlational research. The technique of taking sample was random sampling. The population of this research was 90 students of the second year students of SMP Negeri 3 Bulukumba which belong to three classes. The sample of this research was 45 students. It took from 50% of population, 90 x 50/100 = 45 students. The research data were collected using questionnaires and test. The data were analyzed by using Likert scale and descriptive statistics through SPSS 17.0 version. The research result showed that the second year students of SMP Negeri 3 Bulukumba have high achievement motivation in learning English. This was proven by mean score of achievement motivation 81.57. It was classified into high achievement motivation categories ranges from 68 – 84 score. The students have high self-concept in learning English This was proven by mean score of self-concept 80.24. It was classified into high self-concept categories ranges from 68 – 84 score. The students have moderate socioeconomic status categories. This was proven by mean score of socioeconomic status 64.17. It was classified into moderate socioeconomic status categories ranges from 52 – 68 score. The students have good score in English learning achievement. This was proven by mean score of test 75.71. It was classified into good score in achievement categories ranges from 76 – 85 score. Based on the result of SPSS analysis about the correlation between achievement motivation and English learning achievement was positive and significant with r =  0.757 classified into strong category range from  0.60 – 0.799. The result of SPSS analysis about the correlation between self-concept and English learning achievement was positive and significant with r =  0.803 classified into very strong category range from  0.80 – 1.00. The result of SPSS analysis about the correlation between socioeconomic status  and English learning achievement was positive and significant with r =  0.324 classified into low category range from  0.20 – 0.399.education